Cranial ontogeny of Caluromys philander (Didelphidae, Caluromyinae): a qualitative and quantitative approach - Flores, David Alfredo (2010)
The ontogeny of skull allometry has been the subject of research in didelphid, microbiotheriid, and dasyurid marsupials. We described and compared postweaning stages of cranial development in the woolly opossum Caluromys philander, a member of a distinct lineage of didelphids. We identified 31 qualitative morphological changes between juveniles and adults, many related to the trophic apparatus. Early development of the paracanine fossa in the snout, correlated with the presence of well-developed canines in juveniles, represents a remarkable difference between the ontogeny of C. philander and other marsupials. We performed bivariate and multivariate analyses of allometry on a data set composed of 14 cranial measurements and 45 specimens. Allometric scaling showed that braincase is relatively small in adulthood, whereas other neurocranial components, particularly the orbit, grew isometrically along its length. The palate becomes elongated by the combination of the isometry of its length and the negative allometry of its width. The rostrum lengthened, but its height remained proportionally constant. In relative terms the temporal fossa expanded inward following the marsupial model that combines the negative allometry of the braincase and the isometry of the zygomatic breadth. The mandible increased in robustness. The skull ontogeny of C. philander shares 4 allometric trends with 2 didelphids (Didelphis albiventris and Lutreolina crassicaudata) and two australidelphians (Dromiciops gliroides and Dasyurus albopunctatus). Three of these trends, breadth of palate, breadth of braincase, and height of occipital plate, were allometrically negative, whereas height of the dentary was positive. These common allometric trends may be interpreted as symplesiomorphic for marsupials, suggesting a high degree of conservatism in the skull development of Caluromys and other marsupials.